Perceived Changes Due to COVID-19 Pandemic in Sexual Activity, Sexual Satisfaction, and Life Satisfaction among Indonesian Adults - Ramadhani, Astridiah Primacita; Poerwandari, Elizabeth Kristi (Bina Nusantara University, 2022)
The research sought to find out more about the perceived changes and relationships between sexual activities, sexual satisfaction, and life satisfaction of sexually active Indonesian adults before the pandemic (February 2019 - February 2020) and during the pandemic (March 2020 - June 2020). The research applied a cross-sectional method. An online questionnaire was conducted once in June 2020 to collect the data from 1.006 samples aged 18 to 64. Analysis using paired sample t-test shows a significant decrease due to the COVID-19 pandemic in various sexual activities, including cuddling, non-penetrative sex, masturbation sex, oral sex, and penetrative sex, but not in sexting. The results also show a significant decrease in sexual and life satisfaction due to the COVID-19 pandemic. Regardless of the COVID-19 pandemic, sexual satisfaction, and life satisfaction are positively and significantly correlated in sexually active Indonesian adults. The results of the research indicate that sexual life is still an important aspect, especially when dealing with stressful life events such as the COVID-19 pandemic.